The SARS-CoV-2 epidemic, a school case for public health - Philippe Chossegros (Archives of Preventive Medicine - Peertechz Publications, 2020)
The covid-19 epidemic has evolved differently depending on the responses to it. This heterogeneity and changes in recommendations have blurred the messages facilitating the emergence of fake news and conspiracy theories.